Citizen e-participation in urban governance : crowdsourcing and collaborative creativity - Silva, Carlos Nunes (Information Science Reference, 2013)
"This book explores the nature of the new challenges confronting citizens and local governments in the field of urban governance, exploring the role that Web 2.0 technologies play to promote citizen participation and empowerment in the city government"--Resumé vydavatele
Keywords: crowdsourcing; elektronická veřejná správa; občanská angažovanost; participativní demokracie; místní správa; městská správa; dobrovolníci; spolupráce; electronic government; community involvement; participatory democracy; local government; municipal government; volunteers; cooperation; kolektivní monografie; collective monographs